Brazilian subjectivity today : migration, identity and xenophobia - Simai, Szilvia (2012)
1. Three fantasies of Nation / Szilvia Simai; 2. Foreigner-gringo-brazilian: proximity and distance between brazilians and non-brazilians / Thaddeus Gregory Blanchette; 3. The national myth of receptivity in Brazil: the denial of xenophobia in contemporary society / Rosana Baeninger y Szilvia Simai; 4. The reinvention of Brazil and other metamorphoses in the world of Chicago Samba / Bernadete Beserra; 5. To see oneself through the eyes of the other: gender, race and brazilian identity / Claudia Barcellos Rezende; 6. Subjetive assesments of work opportunities by brazilian women living in Rome / Isabela Cabral Félix de Sousa; 7. "Brazilianness in London: national goods and images in transnational mobilitu / Simone Frangella.--